Detection of Congestive Heart Failure and Myocardial Dysfunction in Cats With Cardiomyopathy by Using Two-Dimensional Speckle-Tracking Echocardiography - Suzuki, Ryohei; Saito, Takahiro; Yuchi, Yunosuke; Kanno, Haruka; Teshima, Takahiro; Matsumoto, Hirotaka; Koyama, Hidekazu (Frontiers in Veterinary Science, 2021)
Congestive heart failure (CHF) is a life-threatening condition in cats with cardiomyopathy. We hypothesized that myocardial dysfunction may induce progression to CHF pathophysiology in cats with cardiomyopathy. However, no previous studies have evaluated the involvement of myocardial dysfunction in cats with CHF. In this study, we aimed to evaluate the relationship between CHF and myocardial function assessed using two-dimensional speckle-tracking echocardiography (2D-STE). Sixteen client-owned healthy cats and 32 cats with cardiomyopathy were enrolled in this study. Cats were classified into three groups: healthy cats, cardiomyopathy without CHF (CM group), and cardiomyopathy with CHF (CHF group). Left ventricular (LV) longitudinal and circumferential strains (SL and SC, respectively), and right ventricular (RV) SL were measured using 2D-STE. Logistic regression analysis was performed to assess the relationship between CHF and echocardiographic variables, including 2D-STE. Results comparing the healthy cats and CM vs. CHF groups showed that increased left atrial to aortic diameter ratio and decreased LV apical SC were significantly associated with the existence of CHF (odds ratio [95% confidence interval]: 1.40 [1.16–1.78] and 1.59 [1.06–2.36], respectively). Results comparing the CM vs. CHF group showed that increased end-diastolic RV internal dimension and decreased RV SL were significantly associated with the existence of CHF (odds ratio: 1.07 [1.00–1.13] and 1.34 [1.07–1.68], respectively). Left atrial enlargement and depressed LV apical myocardial function may be useful tools for predicting the progression to CHF in cats. Furthermore, RV enlargement and dysfunction may lead to the onset of CHF in asymptomatic cats with cardiomyopathy.